Under California stars - Witney, William, 1915-2002; Rogers, Roy, 1911-1998; Republic Pictures Corporation; Cinetel Films ([Burbank, CA] : Republic Pictures Corporation, 1948)
Roy's vacation from movie-making is turned into adventure when wild horse rustlers kidnap Trigger and hold the talented horse for ransom.
Roy Rogers, Jane Frazee, Andy Devine, Trigger, Bob Nolan and the Sons of the Pioneers.
Diector of photography, Jack Marta; editor, Tony Martinelli; musical director, Morton Scott.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Trigger (Horse) -- Drama; Horses -- Drama; Ranch life -- Drama; Horse stealing -- Drama; Cowboys -- Drama; Kidnapping -- Drama; Western films; Fiction films; Feature films; Singing cowboy films; Internet videos; Streaming video